2016
DOI: 10.1093/bjsw/bcw106
|View full text |Cite
|
Sign up to set email alerts
|

Family-Inclusive Approaches to Reablement in Mental Health: Models, Mechanisms and Outcomes

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…• One study examined family-inclusive approaches to reablement in mental health, and defined reablem to maximising users' independence, choice, and quality of life (Tew et al, 2017).…”
mentioning
confidence: 99%
“…• One study examined family-inclusive approaches to reablement in mental health, and defined reablem to maximising users' independence, choice, and quality of life (Tew et al, 2017).…”
mentioning
confidence: 99%
“…The impact of trauma emerged as a sub-theme within a wider national study of wholefamily approaches in mental health, the main findings of which are reported elsewhere (Tew et al, 2017). Ethical approval for the study was obtained from the NRES Committee North-West Cheshire (Ref 12/NW/0102) with research governance approval from local agencies.…”
Section: Methodsmentioning
confidence: 99%
“…Tew et al (61)(62)(63) researched the impact and effectiveness of four types of family interventions, including FGC, with adults experiencing mental ill health in terms of reablement through improved use of personal agency and social interaction. Reablement has been defined as aiming to maximise users' independence, choice and quality of life [(64), p. 4].…”
Section: Fgc Effectiveness In Reablement In Comparison To Three Other Types Of Family Interventionsmentioning
confidence: 99%